Torsion of a functionally graded elastic rod - Ong, Yong Qin (Nanyang Technological University, 2024)
Functionally graded material (FGM) is a unique type of composite that combines two or more homogenous materials to create a microstructure that allows the material’s properties to vary gradually. This helps prevent stress concentration. Although the concept began decades ago, there is still a lack of understanding of their behavior under applied loads. Research and development are still ongoing to understand the stresses experienced by FGMs so that more effective uses of FGMs can be discovered.